TINJAUAN TENTANG HAK WARIS ADAT DALAM TERJADINYA PUTUS WARIS MENURUT HUKUM ADAT MINANGKABAU DI NAGARI SALAYO KABUPATEN SOLOK - Aftahul Jefran; Zulfikar Jayakusuma; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The Minangkabau indigenous people are people who adhere to the Islamicreligion, as has been confirmed in the Minangkabau traditional proverb whichreads Adaik basandi syarak, syarak basandi Kitabullah which means custombased on Islam, religion based on the book of Allah Subhanahu wa Ta'ala . TheMinangkabau people have their own rules in regulating their society, especiallyin the distribution of inheritance. Pusako or pusako property are all tangible(material) assets, which will be inherited later on to nieces and nephews. ThisPusako is a guarantee for the life and equipment of the nephew's childrenMinangkabau.The purpose of writing this thesis, namely: First, to find out inheritancerights in the occurrence of putu inheritance according to Minangkabaucustomary law. Second: To find out the settlement of inheritance rights disputesin the event of inheritance breaking according to Minangkabau customary law.The type of research used in this study is a type of sociological research,which is a part from study law, though there is also which said that socialresearch on law is not legal research.From the results of the study, inheritance rights in the occurrence ofinheritance discontinuation based on Minangkabau customary law are based onthe principle of primacy that applies to the nephew group. However, based oncustomary functionaries, especially those of IV Jinih, Urang Tuo Suku and theChairman of KAN, what applies to determining the right to inherit regardingsako and harto pusako Tinggi people who are extinct is that while alive theperson who is about to become extinct can appoint or have appointed a personwho will inherit the sako . and the pusako , where the appointed person has acondition, namely the freedom of the extinct person to appoint the person whowill inherit his sako and pusako , where the extinct person knows better who iscloser to his people ( tatak indak tasondak, malenggang indak tapampeh ) .Settlement of inheritance disputes according to Minangkabau customary law canbe carried out by traditional leaders or through the courts.Keywords: Heritage-Inheritance-Indigenous Peoples of Nagari Salayo